Greater risks of complications, infections, and revisions in the obese versus non-obese total hip arthroplasty population of 2, 190, 824 patients: a meta-analysis and systematic review. Issue 1 (January 2020) - Onggo, J.R.; Onggo, J.D.; de Steiger, R.; Hau, R.
Summary: Background: Obesity is an epidemic, especially in developed countries. This affects the general health of these patients, especially when they are having a major surgical procedure such as total hip arthroplasty (THA). Several articles have described the effects of obesity on THA with varying conclusions. This meta-analysis aims to compare the outcomes, complications, and peri-operative parameters of THA in the obese (BMI≥30 kg/m 2 ) vs non-obese (BMI<30 kg/m 2 ) population as well as a subgroup analysis of morbidly obese (BMI≥40 kg/m 2 ) vs non-obese population. Methods: A multi-database search was performed according to PRISMA guidelines. Data from studies assessing the outcomes and complications of THA in the obese and non-obese population were extracted and analyzed. Results: Sixty-seven studies were included in this meta-analysis, consisting of 581, 012 obese and 1, 609, 812 non-obese patients. Meta-analysis could not be performed on patient reported outcome measures due to heterogeneous reporting methods. Obese patients had a higher risk of all complications (OR = 1.53, 95%CI: 1.30–1.80, P  < 0.001), deep infections (OR = 2.71, 95%CI: 2.08–3.53, P  < 0.001), superficial infections (OR = 1.99, 95%CI: 1.55–2.55, P  < 0.001), dislocations (OR = 1.72, 95%CI: 1.66–1.79, P  < 0.001), reoperations (OR = 1.61, 95%CI: 1.40–1.85, P  < 0.001), revisions (OR = 1.44, 95%CI: 1.32–1.57, P  < 0.001), and readmissions (OR = 1.37, 95%CI: 1.15–1.63, P  < 0.001). When sub-group analysis of morbidly obese (BMI≥40 kg/m 2 ) patients was performed, the risks of all these parameters were even greater. Conclusion: Obese and morbidly obese patients are at higher risks of complications post THA than non-obese patients. Surgeons should be aware of these risks in order to counsel patients and adopt prophylactic strategies to reduce these risks where applicable.